Tinjauan Yuridis terhadap Sengketa Wakaf dalam Praktik Peradilan Agama - Noor Izzati Amelia; Nur Najwa; Noor Halimah; Nor Harika (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
Waqf is a significant instrument in Islamic teachings that functions not only as a form of worship but also plays a strategic role in enhancing the social and economic welfare of society. However, in practice, waqf often faces various legal challenges, such as the validity of the waqf declaration, the appointment of nazhir (waqf managers), and conflicts between heirs and beneficiaries. This study aims to provide a comprehensive understanding of the strategic position of waqf, analyze the root causes of legal issues that arise in its management, and evaluate the role of the Religious Courts in resolving waqf disputes fairly. The research method used is normative juridical, with a literature review approach focusing on Law Number 41 of 2004 concerning Waqf and various relevant legal sources. The findings reveal that waqf disputes commonly involve issues of legality, asset exchange or sale, and the annulment of waqf declarations. The study also identifies disparities in judicial decisions, influenced by differences in the judges’ educational backgrounds and legal approaches. Therefore, there is a need to strengthen national jurisprudence as a reference in waqf-related cases, provide training for nazhir to enhance professionalism, improve the capacity of judges in Religious Courts, and promote legal education among the public. These efforts are expected to create a more just, consistent, and effective dispute resolution system, thereby supporting the productive and sustainable management of waqf assets.